FAKTOR RESIKO PEROKOK DAN KADAR LEUKOSIT DENGAN KEJADIAN KETUBAN PECAH DINI DI RUANG BERSALIN RSD DR. SOEBANDI JEMBER - Wahda, Nurul; Gumiarti, Gumiarti; Susilawati, Susilawati (Malang Journal of Midwifery (MAJORY), 2025)
Premature rupture of membranes (KPD) is one of the important complications and problems in obstetrics which is associated with increased perinatal morbidity and mortality. According to WHO, the incidence of KPD ranges from 12%-14%. In Indonesia, KPD ranges from 4.4-7.6% of all pregnancies. At RSD Dr. Soebandi in 2023, the highest referral case is KPD with an incidence of 17.4%. The aim of the study was to determine the risk factors of smoking and leukocyte levels with the incidence of PROM at RSD dr. Soebandi Jember. The research was a quantitative study with an analytical observational design using a cross-sectional approach. The population consisted of 125 postpartum mothers, and the sample size was determined using the Slovin formula, resulting in 95 respondents. The sampling technique used was accidental sampling. The measurement tool was a questionnaire, and data analysis was conducted using the Prevalence Ratio test. 77.90% of mothers giving birth were passive smokers, 77.90% of women gave birth with normal leukocyte levels, 50.50% of women gave birth with premature rupture of membranes, analysis of passive smokers with the incidence of KPD was found to be RP 1.2 with 95% CI (0.559-3.948), abnormal leukocyte levels with the incidence of PROM were found to be RP 1.6 with a 95% CI (1.085-8.893). Passive smoking is not a risk factor for premature rupture of membranes, while abnormal leukocyte levels carry a 1.6 times greater risk compared to women giving birth with normal leukocyte levels. It is expected that pregnant women will improve personal hygiene and become more proactive in getting their pregnancies checked as a preventive measure against the increase in leukocyte levels during pregnancy.